Descriptive Study: Implementation Of Keyboard Musical Instrument Learning Method For Students With Visual Disabilities At SLB N Branjangan Indonesia - Zumar, Fajar Rafi; Lailil , Aflahkul Yaum; Sugihartatik, Sugihartatik (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The purpose of this study was to describe the learning methods used in learning to use keyboard musical instruments for students with visual disabilities at SLB N Branjangan. This research uses a qualitative descriptive approach, with a case study approach with data collection techniques through observation, interviews and documentation with the research subjects being music teaching teachers and SLB students who take part in learning Keyboard musical instruments. The results of this study indicate that the implementation of keyboard musical instrument learning methods for students with visual disabilities in SLB N Branjangan includes planning, implementation and evaluation. Planning is done by compiling some material that will be studied specifically by students with visual disabilities, then in the implementation of learning using mixed methods in one face-to-face meeting consisting of lecture methods, demonstration / direct practice methods and exercise methods. the lecture method is carried out in a classical or comprehensive manner, while the demonstration method is carried out individually or alternately, while the evaluation is carried out by the teacher of each student at the end of the keyboard music lesson individually by asking questions and students are ordered to practice or play keyboard musical instruments